2023
DOI: 10.1021/acsnano.3c07763
|View full text |Cite
|
Sign up to set email alerts
|

Nanomedicine Strategies in Conquering and Utilizing the Cancer Hypoxia Environment

Yi Pan,
Longcai Liu,
Xiaozhou Mou
et al.

Abstract: Cancer with a complex pathological process is a major disease to human welfare. Due to the imbalance between oxygen (O 2 ) supply and consumption, hypoxia is a natural characteristic of most solid tumors and an important obstacle for cancer therapy, which is closely related to tumor proliferation, metastasis, and invasion. Various strategies to exploit the feature of tumor hypoxia have been developed in the past decade, which can be used to alleviate tumor hypoxia, or utilize the hypoxia for targeted delivery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 393 publications
(709 reference statements)
0
3
0
Order By: Relevance
“…This is because rapidly growing malignant tumors disrupt the balance between oxygen consumption and supply, leading to a hypoxic environment inside cancer cells. The hypoxic environment of cancer cells activates a series of cascading factors, and the interaction of these factors contributes to issues such as cancer metastasis, invasion, resistance changes, and poor prognosis [28][29][30][31]. Therefore, we examined the changes in DKK2 under simulated in vivo hypoxic conditions and confirmed that the expression of DKK2 increases under hypoxic conditions.…”
Section: Discussionmentioning
confidence: 95%
“…This is because rapidly growing malignant tumors disrupt the balance between oxygen consumption and supply, leading to a hypoxic environment inside cancer cells. The hypoxic environment of cancer cells activates a series of cascading factors, and the interaction of these factors contributes to issues such as cancer metastasis, invasion, resistance changes, and poor prognosis [28][29][30][31]. Therefore, we examined the changes in DKK2 under simulated in vivo hypoxic conditions and confirmed that the expression of DKK2 increases under hypoxic conditions.…”
Section: Discussionmentioning
confidence: 95%
“…40 Tumor hypoxia is an important cause of immune escape in solid tumors and inhibits the function of T cells and increases the number of immunosuppressive cells. 167 168 Improving tumor hypoxia is a potential strategy for enhancing pyroptosis-based tumor therapy.…”
Section: Internationalmentioning
confidence: 99%
“…Cancer, a disease with a high mortality rate, has emerged as a major serious health problem, posing threat to humanity. 1–3 In order to effectively treat cancer and improve survival rates, the development of imaging strategies capable of detecting tumors has become a hot topic of research. 4,5 Traditional imaging techniques, such as radiography, computed tomography (CT) and magnetic resonance imaging (MRI), face difficulties in directly monitoring biological phenomena on a real time scale.…”
Section: Introductionmentioning
confidence: 99%